PROSES DAN LEMBAGA PENYIDIKAN PADA TINDAK PIDANA KORUPSI - Umi Enggarsasi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
The corruption in Indonesia has been spread-out badly and systematically causing great financial loss and furthermore, the violation of social and economic rights. Therefore it is classified as a special crime, that should be wiped out in special way too. The Corruption Watch Committee is an independent organization, working based on KUHAR except ps. 7. The investigation conducted according to ps. 45 to ps. 50 UU No. 2001 of Corruption Watch Committee.